Pengaruh Faktor Kemudahan, Keamanan, dan Resiko Terhadap Kepuasan Nasabah Dalam Menggunakan Mobile Banking (Studi Kasus Pada Nasabah BRI Kabupaten Mamuju) - Kamarudin, Jamaludin; Nursiah, Nursiah; Novianti, Melisa (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
Mobile banking is a facility provided by banks in the form of applications that can be accessed by customers by utilizing the internet network in carrying out various transaction activities such as checking balances, transfers, and paying various dues or household bills. This study aims to measure how much influence the factors of convenience, security, and risk have on customer satisfaction in using mobile banking. The variables used in this research are convenience factor (X1), security factor (X2), risk factor (X3), and customer satisfaction (Y). The method used in this research is using the accidental sampling method by distributing questionnaires to 40 customer respondents of Bank Rakyat Indonesia, Mamuju Regency. The analysis technique used is multiple linear regression analysis to measure the effect partially and simultaneously. The results obtained show that there is a positive and significant influence between the convenience factor and the security factor on customer satisfaction, and a negative and insignificant effect between risk factors on customer satisfaction in using mobile banking.